AB1058 The New Joint Weighted Scoring System Which Predicts The Modified Health Assessment Questionnaires Scores in Rheumatoid Arthritis Patients: A Validation Study Using The National Database of Rheumatic Diseases by iR-net in Japan. (15th July 2016) - Ono, K.; Ohashi, S.; Oka, H.; Kadono, Y.; Omata, Y.; Matsumoto, T.; Izawa, N.; Nishino, J.; Tanaka, S.; Tohma, S.
Abstract : Background: We reported the impact of each joint disease on the MHAQ (Modified Health Questionnaire) by using 2011 NinJa (the National Database of Rheumatic Diseases by iR-net in Japan) data in the past study. The odds ratio of physical impairment according to the MHAQ using multivariable logistic regression models for bilateral and unilateral joints, respectively, were: shoulder, 4.0 and 1.8; elbow, 2.6 and 1.8; wrist, 1.9 and 1.5; hip, 1.7 and 3.0; knee, 2.6 and 1.9; ankle, 2.3 and 2.0; finger, 1.4 and 1.2; and toe, 1.0 and 1.1. The MHAQ score was significantly affected by shoulder, elbow, wrist, knee, and ankle joint disease, and bilateral disease tended to have a greater effect on physical impairment than unilateral disease. We also developed a joint weighted scoring system from the results of the odds ratio. An integer score was assigned to each identified bilateral and unilateral joint disease, respectively, as follows: shoulder, 4 and 2; elbow, 3 and 2; wrist, 2 and 2; hip, 0 and 3; knee, 3 and 2; ankle, 2 and 2; finger, 1 and 1. We acquired 3 points as the cut-off value of this scoring system through statistical analysis (Modern Rheumatology, 2015, Epub ahead of print). Objectives: To validate this scoring system by applying to NinJa in 2014. Methods: A total of 13, 459 subjects (2, 586 men, 10, 873 female) from NinJa in 2014 were analyzed. The presence or absence of disease in each joint (swelling and/or tenderness were considered as disease) and whether the disease was unilateral or bilateral were investigated. ROC curve analysis was performed to each patient with total score calculated according to the scoring system. Results: The patients' mean age and disease duration was 64.1 and 13.0 years, respectively. The Disease Activity Score-28CRP was 2.4. ROC analysis' results were as follows: cut-off value, 3 points; AUC, 0.68; sensitivity, 53.4%; and specificity, 75.0%. Conclusions: This joint weighted scoring system was validated and suggested to be useful to predict of functional disability of RA patients in a daily practice. Disclosure of Interest: None declared